Methylglyoxal suppresses human colon cancer cell lines and tumor growth in a mouse model by impairing glycolytic metabolism of cancer cells associated with down-regulation of c-Myc expression. Issue 9 (1st September 2016) - He, Tiantian; Zhou, Huaibin; Li, Chunmei; Chen, Yuan; Chen, Xiaowan; Li, Chenli; Mao, Jiating; Lyu, Jianxin; Meng, Qing H.
ABSTRACT: Methylglyoxal (MG) is a highly reactive dicarbonyl compound exhibiting anti-tumor activity. The anti-tumor effects of MG have been demonstrated in some types of cancer, but its role in colon cancer and the mechanisms underlying this activity remain largely unknown. We investigated its role in human colon cancer and the underlying mechanism using human colon cancer cells and animal model. Viability, proliferation, and apoptosis were quantified in DLD-1 and SW480 colon cancer cells by using the Cell Counting Kit-8, plate colony formation assay, and flow cytometry, respectively. Cell migration and invasion were assessed by wound healing and transwell assays. Glucose consumption, lactate production, and intracellular ATP production also were assayed. The levels of c-Myc protein and mRNA were quantitated by western blot and qRT-PCR. The anti-tumor role of MG in vivo was investigated in a DLD-1 xenograft tumor model in nude mice. We demonstrated that MG inhibited viability, proliferation, migration, and invasion and induced apoptosis of DLD-1 and SW480 colon cancer cells. Treatment with MG reduced glucose consumption, lactate production, and ATP production and decreased c-Myc protein levels in these cells. Moreover, MG significantly suppressed tumor growth and c-Myc expression in vivo . Our findings suggest that MG plays an anti-tumor role in colon cancer. It inhibits cancer cell growth by altering the glycolytic pathwayassociated with downregulation of c-Myc protein. MG has therapeutic potential in colon cancer by interrupting cancer metabolism.